2021
DOI: 10.1093/jxb/erab074
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide analysis of epitranscriptome and translational efficiency associated with heterosis in maize

Abstract: Heterosis has been extensively utilized to increase productivity in crop, yet underlying molecular mechanisms remain largely elusive. Here, we generated transcriptome-wide profiles of mRNA abundance, m 6A methylation, and translational efficiency from the maize F1 hybrid B73×Mo17 and its two parental lines to ascertain contributions of each regulatory layer to heterosis at the seedling stage.We documented that although the global abundance and distribution configuration of m 6A maintained unchanged, a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 102 publications
3
15
0
Order By: Relevance
“…In summary, these results implied a more general conservation pattern of m 6 A methylation in plants, which could be related to the fundamental role of m 6 A methylation in plant development (Zhong et al, 2008 ; Shen et al, 2016 ; Anderson et al, 2018 ). Nevertheless, a recently published study showed that there are much more genes with differentially m 6 A level or non-additively m 6 A variation in maize hybrid (B73 × Mo17) compared with the parents (Luo et al, 2021 ), implying that the pattern of m 6 A reprogramming in hybrid is related to species or parent lines with different degree of variation.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these results implied a more general conservation pattern of m 6 A methylation in plants, which could be related to the fundamental role of m 6 A methylation in plant development (Zhong et al, 2008 ; Shen et al, 2016 ; Anderson et al, 2018 ). Nevertheless, a recently published study showed that there are much more genes with differentially m 6 A level or non-additively m 6 A variation in maize hybrid (B73 × Mo17) compared with the parents (Luo et al, 2021 ), implying that the pattern of m 6 A reprogramming in hybrid is related to species or parent lines with different degree of variation.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression in hybrids is affected by cis -acting elements, trans -acting factors, and their interaction ( Birchler and Veitia, 2010 ). Cis -regulatory elements are short DNA sequences containing trans-factor-specific binding sites that are used to control the expression of their associated genes ( Bao et al, 2019 ; Luo et al, 2021 ). It can lead to changes in gene expression, and in hybrids, different regulatory factors and transcriptional networks recombine ( Birchler et al, 2003 ; Riddle and Birchler, 2003 ; Zhang et al, 2008 ; Bougas et al, 2010 ).…”
Section: Transcriptomics and Proteomics Reveal Plant Heterosismentioning
confidence: 99%
“…The rapid development of sequencing technology has made it possible to explore heterosis at the molecular level [ 5 ], and it has been used in many species, such as Arabidopsis [ 6 – 8 ], rice [ 9 11 ], maize [ 12 , 13 ], and wheat [ 14 , 15 ]. These studies combined morphological and omics techniques to analyze the changes in the vegetative and reproductive growth phases of hybrids relative to their parents.…”
Section: Introductionmentioning
confidence: 99%